Influence of pollution control on lead inhalation bioaccessibility in PM2.5: A case study of 2014 Youth Olympic Games in Nanjing. (September 2016) - Li, Shi-Wei; Li, Hong-Bo; Luo, Jun; Li, Hui-Ming; Qian, Xin; Liu, Miao-Miao; Bi, Jun; Cui, Xin-Yi; Ma, Lena Q.
Abstract: Pollution controls were implemented to improve the air quality for the 2014 Youth Olympic Games (YOG) in Nanjing. To investigate the influence of pollution control on Pb inhalation bioaccessibility in PM2.5, samples were collected before, during, and after YOG. The objectives were to identify Pb sources in PM2.5 using stable isotope fingerprinting technique and compare Pb inhalation bioaccessibility in PM2.5 using two simulated lung fluids. While artificial lysosomal fluid (ALF) simulates interstitial fluid at pH 7.4, Gamble's solution simulates fluid in alveolar macrophages at pH 4.5. The Pb concentration in PM2.5 samples during YOG (88.2 ng m − 3 ) was 44–48% lower than that in non-YOG samples. Based on stable Pb isotope ratios, Pb in YOG samples was mainly from coal combustion while Pb in non-YOG samples was from coal combustion and smelting activities. While Pb bioaccessibility in YOG samples was lower than those in non-YOG samples (59–79% vs. 55–87%) by ALF, it was higher than those in non-YOG samples (11–29% vs. 5.3–21%) based on Gamble's solution, attributing to the lower pH and organic acids in ALF. Different Pb bioaccessibility in PM2.5 between samples resulted from changes in Pb species due to pollution control. PbSO4 was the main Pb species in PM2.5 from coal combustion, which was less soluble in ALF than PbO from smelting activities, but more soluble in Gamble's solution. This study showed it is important to consider Pb bioaccessibility during pollution control as source control not only reduced Pb contamination in PM2.5 but also influenced Pb bioaccessibility. Graphical abstract: Highlights: Stable isotope was used to trace changes in Pb sources in PM2.5 . Artificial lysosomal fluid and Gamble's solution for Pb inhalation bioaccessibility in PM2.5 . Both coal combustion and smelting contribute to Pb sources in PM2.5 . Pollution control decreased PM2.5 and total Pb concentrations in Nanjing. Pollution control changed Pb inhalation bioaccessibility in PM2.5 .